INCREASED RISK OF MYCOBACTERIUM TUBERCULOSIS INFECTION IN HOUSEHOLD CHILD CONTACTS EXPOSED TO PASSIVE TOBACCO SMOKE - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Risk factors associated with Mycobacterium tuberculosis infection were investigated in a prospective cohort of household child tuberculosis contacts. A significantly increased risk of acquiring infection was associated with exposure to passive cigarette smoke, higher number of index cases, younger age and reduced household monthly income.
Keywords: childhood tuberculosis; infection; interferon-gamma release assay; smoking; CELL-BASED DIAGNOSIS; PREVALENCE